From Mimbar to Mouse: Adapting Islamic Education to the Digital Age - Rifa’i, Feri Lukman; Al Mubarok, Fahmi Ulum; Maksum, Muh Nur Rochim; Mustofa, Triono Ali (Universitas Muhammadiyah Surakarta, 2024)
The transformation of traditional Islamic education in the digital age marks a significant shift in teaching methods influenced by technological advancements. This study explores how Islamic education adapts to modern technology, emphasizing the integration of digital tools into curricula and instructional practices. The primary objective is to examine the impact of this transformation on students' learning experiences, teachers' roles, and institutional dynamics within Islamic education. Using qualitative research methods, including in-depth interviews, digital content analysis, and participant observation, this study seeks to provide a comprehensive understanding of both the challenges and opportunities presented by digital adaptation. The findings aim to offer valuable insights for educators, policymakers, and institutional leaders in Islamic education, helping them develop effective strategies to ensure that digital integration enhances rather than compromises the essence of Islamic learning. By bridging traditional teachings with technological advancements, this research contributes to shaping a more accessible, engaging, and sustainable Islamic education system in the digital era.